2011
DOI: 10.1016/j.meegid.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the Hepatitis B virus genotypes in Colombia: A Bayesian inference on the genotype F

Abstract: Hepatitis B is a worldwide health problem affecting about 2 billion people and more than 350 million are chronic carriers of the virus. Nine HBV genotypes (A to I) have been described. The geographical distribution of HBV genotypes is not completely understood due to the limited number of samples from some parts of the world. One such example is Colombia, in which few studies have described the HBV genotypes. In this study, we characterized HBV genotypes in 143 HBsAg-positive volunteer blood donors from Colomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 63 publications
3
50
0
4
Order By: Relevance
“…HBV genotypes F and H are considered indigenous to the American continent [15,17,18]. An HBV strain isolated from woolly monkey (a New World monkey) is closer to genotype F but with a noteworthy phylogenic distance from other strains of HBV [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV genotypes F and H are considered indigenous to the American continent [15,17,18]. An HBV strain isolated from woolly monkey (a New World monkey) is closer to genotype F but with a noteworthy phylogenic distance from other strains of HBV [19].…”
Section: Resultsmentioning
confidence: 99%
“…These samples were initially subgenotyped using a system developed in the Clinical Laboratory [23] and were then selected for a longer fragment (1306 bp) amplification using other previously described primers [18]. …”
Section: Resultsmentioning
confidence: 99%
“…The studies of HBV genotyping in different populations revealed that in the Andean region of Colombia, genotype F, subgenotype F3, is the most prevalent, while genotype F1b is the most frequent in Amazonas state (South East) and genotype A is the most common in the Pacific region of the country; even though genotypes D, C, G and E have also been described in the Colombian populations [32, 61, 8891]. In the present study, the genetic analysis of the viral genome revealed the predominance of genotype F (three cases); subgenotype F1 was identified in one case while F3 was identified in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…Each Bayesian MCMC analysis was run for 20 million states and sampled at every 10,000 states. Posterior probabilities were calculated with a burn-in of 2 million states and checked for convergence using Tracer (v1.5 [30]). …”
Section: Methodsmentioning
confidence: 99%